2009
DOI: 10.1007/s11164-009-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of photocatalytic activity of Cd-doped mesoporous nanocrystalline TiO2 prepared at low temperature

Abstract: Mesoporous nanocrystalline Cd-doped titania was firstly prepared at low temperature by a modified sol-gel method, using dodecylamine as a template. The template could be easily removed by refluxing samples in nitric acid ethanol solution. The Fourier transform infrared spectrometer (FT-IR), low-angle and wideangle X-ray diffraction (XRD), N 2 adsorption-desorption, transmission electron microscopy (TEM), X-ray photoelectron spectra (XPS), and UV-visible diffuse reflectance spectroscopy were used for the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The mechanism of cation doping is essentially to tune the Fermi level and electronic structure of d-electron configuration in TiO 2 , thereby to tune the energy levels to absorb the visible light energy and to enhance the overall photocatalytic efficiency of the system as shown in Figure 4a Consequently, there have been many cations doped in TiO2 towards enhancing its PC activities. In such cation doping, TiO2 has been doped with the (i) transition metals such as Sc, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Cd, and W [73][74][75][76][77][78][79][80][81][82][83][84]; (ii) rare-earth metals such as Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Er, Yb, and La [85][86][87][88][89]; and (iii) other metals such as Li, Mg, Ca, Se, Sr, Al, Sn, and Bi [90][91][92][93][94][95][96][97]. In the case of rare earth elements doping, the electronic configurations such as 4f, 5d, and 6s are found to be favorable to tune the band edge positions, density of states, and width of VB and CB via altering the crystal, electronic, and optical structures in TiO2 [98][99][100].…”
Section: Cationic Doping In Tiomentioning
confidence: 99%
“…The mechanism of cation doping is essentially to tune the Fermi level and electronic structure of d-electron configuration in TiO 2 , thereby to tune the energy levels to absorb the visible light energy and to enhance the overall photocatalytic efficiency of the system as shown in Figure 4a Consequently, there have been many cations doped in TiO2 towards enhancing its PC activities. In such cation doping, TiO2 has been doped with the (i) transition metals such as Sc, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Cd, and W [73][74][75][76][77][78][79][80][81][82][83][84]; (ii) rare-earth metals such as Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Er, Yb, and La [85][86][87][88][89]; and (iii) other metals such as Li, Mg, Ca, Se, Sr, Al, Sn, and Bi [90][91][92][93][94][95][96][97]. In the case of rare earth elements doping, the electronic configurations such as 4f, 5d, and 6s are found to be favorable to tune the band edge positions, density of states, and width of VB and CB via altering the crystal, electronic, and optical structures in TiO2 [98][99][100].…”
Section: Cationic Doping In Tiomentioning
confidence: 99%
“…Andronic et al [18] reported that there was a linear correlation between the band gap energy of the Cd-doped TiO 2 films and dyes photodegradation efficiency. Cd-doped mesoporous titania had high visiblelight photocatalytic activities [19]. Whether as interstitial atom or lattice atom displacement, metal doping introduces impurity states between valance band (VB) and conduction band (CB), which act as electrons and holes recombination centers and can capture most of the charge carrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lifetime of reactive oxygen species is relatively short under UV irradiation, which often led to a partial mineralization of organic pollutants [11]. Mesoporous TiO 2 has been considered to be a promising photocatalyst owing to its advantages such as high specific surface area and multidimensional framework [12][13][14]. Kim et al have reported that the photocatalytic activity of mesoporous TiO 2 was 5.8 times higher than that of Degussa P25 TiO 2 in the degradation of methylene blue [14].…”
Section: Introductionmentioning
confidence: 99%